Evaluate Professİonal and Amateur Athletes' Socıal Insurances wıth Legal Aspects In Turkey - Hüseyin Fatih Şen; Arif Özsarı; Mehmet Altın; Alpaslan Görücü; Bülent Fişekçioğlu (Selcuk University, 2019)
With this study, we aimed to evaluate professional and amateur athletes' social insurances with legal aspects in Turkey.In this study -which was prepared by making use of descriptive analysis- related laws, regulations and literature were reviewed and the recent situation was demonstrated by researching the obtained resources. It's understood that professional and amateur Athletes' contracts are a sort of service contracts, but neither group is subject to Labor Law No. 4857, therefore they cannot demand severance pay, notice pay or annual leave; and that general and special provisions of  Law on Debts No. 6098 were implemented for the athletes who signed a contract with a club; and it is also understood that state athletes, jockeys and foreign athletes were subject to the Law On Social Insurance and General Health Insurance No.5510; and that, amateur athletes who have a contract with a club were evaluated in the scope of private health insurance, despite that, amateur athletes without contract to any club aren't subject to social insurance provisions